1997
DOI: 10.1192/pb.21.10.600
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acute psychiatric readmission

Abstract: A retrospective case note study explored réadmissions to an acute psychiatric in-patient unit within six months of discharge. The study aimed to calculate a hospital readmission rate, to investigate the timing of readmissions, and to identify risk factors associated with readmission. The readmission rate was 27% with the majority of readmissions occurring within three months after discharge, suggesting the need for investigation of such early readmissions. The three factors found to predict readmission were: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
0
10
0
3
Order By: Relevance
“…Living in care (vs alone or with family) was found as a protective factor in Dixon et al [30], and Russo et al [59] found homelessness as a risk factor at bivariate level, while living alone was found as protective in Priebe [14] and in Adams [60]. In Ono et al [18], the variable “number of cohabitants” was considered, a larger number turning out to be a protective factor for readmission.…”
Section: Categories Of Pre-discharge Variables Analysedmentioning
confidence: 99%
“…Living in care (vs alone or with family) was found as a protective factor in Dixon et al [30], and Russo et al [59] found homelessness as a risk factor at bivariate level, while living alone was found as protective in Priebe [14] and in Adams [60]. In Ono et al [18], the variable “number of cohabitants” was considered, a larger number turning out to be a protective factor for readmission.…”
Section: Categories Of Pre-discharge Variables Analysedmentioning
confidence: 99%
“…Four known previous studies have investigated factors that predict re-admission to a psychiatric hospital within the United Kingdom (Hodgson et al, 2001;Langdon et al, 2001;Dixon, Robertson, George, & Oyebode, 1997;Tyrer et al, 1995). Hodgson et al (2001) examined data on admissions in an area of Britain from 1987 to 1993 and reported higher re-admission rates for those who were unmarried, had a diagnosis of psychotic disorder, detained under sections of the Mental Health Act, or had a shorter length of stay during their index admission.…”
mentioning
confidence: 98%
“…Hodgson et al (2001) examined data on admissions in an area of Britain from 1987 to 1993 and reported higher re-admission rates for those who were unmarried, had a diagnosis of psychotic disorder, detained under sections of the Mental Health Act, or had a shorter length of stay during their index admission. Dixon et al (1997) examined factors that were related to re-admission to hospital within six months of discharge. They reported that having more prior admissions, living alone or with family, and being discharged against medical advice predicted re-admission.…”
mentioning
confidence: 99%
“…17 Of particular concern is the impact of current pressure to shorten length of hospital stay, which is hypothesized to result in premature discharge and put the patient at risk of readmission. [18][19][20] If readmission is to be considered an indicator of the quality of hospital care, it should be actionable by hospitals, that is, a change in hospital practice should influence the indicator result. 21 Furthermore, the authors should be able to offer some guidelines on acceptable results.…”
mentioning
confidence: 99%